Firewalls for Dummies 2nd Edition - Komar, Brian (Wiley Publishing, 2011)
Firewalls For Dummies® helps you understand what firewalls are, how they operate on different types of networks, what they can and can’t do, and how to pick a good one (it’s easier than identifying that perfect melon in the supermarket.) You’ll find out about